Catalytic Cleavage of the C-O Bond in 2,6-dimethoxyphenol Without External Hydrogen or Organic Solvent Using Catalytic Vanadium Metal - Yu, Peng; Xie, Xue; Tan, Pengfei; Zhang, Wei; Wang, Zhiguo; Zhang, Chun; Liu, Hui (Frontiers in Chemistry, 2020)
Hydrogenolysis of the C-O bonds in lignin, which promises to be able to generate fuels and chemical feedstocks from biomass, is a particularly challenging and important area of investigation. Herein, we demonstrate a vanadium-catalyzed cleavage of a lignin model compound (2,6-dimethoxyphenol). The impact of the catalyst in the context of the temperature, reaction time and the solvent, was examined for the cleavage of the methyl ethers in 2,6-dimethoxyphenol. In contrast to traditional catalytic transfer hydrogenolysis, which requires high pressure hydrogen gas or reductive organic molecules, such as an alcohol and formic acid, the vanadium catalyst demonstrates superior catalytic activity on the cleavage of the C-O bonds using water as a solvent. For example, the conversion of 2,6-dimethoxyphenol is 89.5 % at 280 °C after 48 hours using distilled water. Notably, the vanadium-catalyzed cleavage of the C-O bond linkage in 2,6-dimethoxyphenol affords 3-methoxycatechol, which undergoes further cleavage to afford pyrogallol. This work is expected to provide an alternative method for the hydrogenolysis of lignin and related compounds into valuable chemicals in the absence of external hydrogen and organic solvents.